THE EFFECT OF ACUPRESSURE AND AROMATHERAPY LAVENDER INTEREST TO REDUCE THE LEVEL OF ANXIETY IN CHRONIC KIDNEY FAILURE PATIENTS TREATING HEMODIALIZATION THERAPY IN THE HEMODIALIZATION ROOM OF BSD MEDIKA HOSPITAL TANGERANG - Ayamah, Ayamah; Holidah, Holidah; Hakim, Amelia Nurul; Setiawan, Heri; Handoyo, Lukman (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2024)
ABSTRACTChronic kidney failure is the inability of kidney function to maintain the body's metabolism, resulting in progressive destruction of kidney structures. Chronic kidney disease that has reached the end stage and the kidneys are no longer functioning, kidney replacement therapy is needed, namely dialysis (hemodialysis). Patients with kidney failure who undergo hemodialysis in the long term will face various problems, one of which is anxiety. The purpose of this study was to determine the effect of acupressure and lavender flower aromatherapy on reducing anxiety in Chronic Kidney Failure patients undergoing hemodialysis therapy at BSD Medika Hospital Tangerang. This research method is a quantitative method with a pre-experimental design using One Group PreTest Post Test Design. The number of samples is 30 respondents, using simple random sampling technique. The tools for data collection used the Hamilton Anxiety Rating Scale (HARS) instrument and the observation sheet for Acupressure Therapy and Lavender Aromatherapy. The results showed a decrease in anxiety levels in chronic kidney failure patients undergoing hemodialysis, the average decrease in anxiety levels in chronic kidney failure patients after being given acupressure therapy and lavender flower aromatherapy got a value of 19.1. Based on data analysis using the Wilcoxon Signed Rank Test statistical test. The results of this experimental study indicate that it has a p-value smaller than 0.05 which is 0.000 so that the hypothesis is accepted (Hₐ), it can be concluded that there is an effect of acupressure and lavender flower aromatherapy therapy at BSD Medika Hospital Tangerang. It is suggested that the results of this study can be used as a guide in overcoming anxiety in patients undergoing hemodialysis therapy by using complementary therapies, namely acupressure therapy and lavender flower aromatherapy. ABSTRAKGagal ginjal kronis adalah ketidakmampuan fungsi ginjal dalam menjaga metabolisme tubuh sehingga mengakibatkan kerusakan struktur ginjal secara progresif. Penyakit ginjal kronis yang sudah mencapai stadium akhir dan ginjal tidak berfungsi lagi maka diperlukan terapi pengganti ginjal yaitu cuci darah (hemodialisis). Penderita gagal ginjal yang menjalani hemodialisis dalam jangka waktu lama akan menghadapi berbagai permasalahan, salah satunya adalah kecemasan. Tujuan penelitian ini adalah untuk mengetahui pengaruh akupresur dan aromaterapi bunga lavender terhadap penurunan kecemasan pada pasien Gagal Ginjal Kronis yang menjalani terapi hemodialisis di RS Medika BSD Tangerang. Metode penelitian ini adalah metode kuantitatif dengan desain pra-eksperimental dengan menggunakan One Group PreTest Post Test Design. Jumlah sampel sebanyak 30 responden, pengambilan sampel dengan menggunakan teknik simple random sampling. Alat pengumpulan data menggunakan instrumen Hamilton Anxiety Rating Scale (HARS) dan lembar observasi Terapi Akupresur dan Aromaterapi Lavender. Hasil penelitian menunjukkan adanya penurunan tingkat kecemasan pada pasien gagal ginjal kronik yang menjalani hemodialisa, rata-rata penurunan tingkat kecemasan pada pasien gagal ginjal kronik setelah diberikan terapi akupresur dan aromaterapi bunga lavender mendapat nilai sebesar 19,1. Berdasarkan analisis data menggunakan uji statistik Wilcoxon Signed Rank Test. Hasil penelitian eksperimental ini menunjukkan memiliki p-value lebih kecil dari 0,05 yaitu 0,000 sehingga hipotesis diterima (Hₐ), maka dapat disimpulkan terdapat pengaruh terapi akupresur dan aromaterapi bunga lavender di RS Medika BSD. tangerang. Disarankan hasil penelitian ini dapat dijadikan pedoman dalam mengatasi kecemasan pada pasien yang menjalani terapi hemodialisis dengan menggunakan terapi komplementer yaitu terapi akupresur dan aromaterapi bunga lavender.